L2 Vocabulary Learning From Reading: Explicit and Tacit Lexical Knowledge and the Role of Learner and Item Variables. Issue 2 (28th April 2014) - Elgort, Irina; Warren, Paul
<x xml:space="preserve">Abstract</x> This study investigates acquisition of second language (L2) vocabulary from reading a connected authentic text. Advanced and upper‐intermediate L2 (English) participants read a long expository text for general understanding, with embedded critical vocabulary items (pseudowords). Explicit knowledge of the critical items was examined using a meaning generation task, while their tacit knowledge was probed using form and semantic priming in lexical decision tasks. Results revealed a complex landscape of contextual L2 word learning in which individual differences (age, L2 lexical proficiency, first language, gender, learning strategies, levels of enjoyment) and lexical and text characteristics (concreteness, frequency, distribution, and saliency of use) individually and together affect L2 lexical development from reading. Implications of these results for contextual L2 word learning are discussed.